2020
DOI: 10.1186/s13104-020-04950-5
|View full text |Cite
|
Sign up to set email alerts
|

Population-level investigation of the knowledge of ocular chemical injuries and proper immediate action

Abstract: Objective: Although the eyes occupy 0.1% of the total body surface, eye injuries are serious because vision is arguably the most important sense. We aimed to assess knowledge of Saudi Arabian residents regarding steps to be taken in cases of chemical eye injury, in order to promote awareness of such procedures. Results: A cross-sectional design was done. A random sampling method was utilized to select 888 individuals in the Saudi community. Participants completed an electronic closed ended, validated, anonymou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 8 publications
1
7
1
Order By: Relevance
“…These high prevalence rates warrant research into community's level of knowledge of chemical eye injuries to reduce their incidence and complications. The analysis showed that the vast majority (95.1%) agreed that chemical injuries to the eye can cause ocular complications; a finding consistent with studies from Jeddah [ 9 ] (88.3%) and Aseer region (86.9%) [ 10 ].…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…These high prevalence rates warrant research into community's level of knowledge of chemical eye injuries to reduce their incidence and complications. The analysis showed that the vast majority (95.1%) agreed that chemical injuries to the eye can cause ocular complications; a finding consistent with studies from Jeddah [ 9 ] (88.3%) and Aseer region (86.9%) [ 10 ].…”
Section: Discussionsupporting
confidence: 81%
“…In a similar investigation of chemical eye injuries among the general population of Jeddah, Seraj et al. reported half this prevalence rate (15.5%) [ 9 ]. This may be explained by different methodological approaches to the question regarding the history of ocular chemical injuries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations